Health Literacy on Cataract and Its Treatment Options Among Patients with Operable Cataract: A Cross Sectional Study from Moradabad (India) - Richa Gupta; Akansha Gupta; Mossab Omair; Lokesh Chauhan; Pradeep Agarwal; Ashi Khurana (Delhi Journal of Ophthalmology)
Purpose: To investigate the awareness of cataract disease and treatment options among patients with operable cataract. Methods: Participants were selected by means of eye disease screenings throughout Moradabad district. A pre-tested structured, content-validated questionnaire, translated in Hindi, was used for seeking study-related information and consisted of three sections: 1) Socio-demographic characteristics, 2) Knowledge and 3) Attitude of patients regarding cataract and its treatment. Questionnaire was administered by a trained interviewer after it was determined that the patient needed cataract surgery. Results: A total of 192 participants were interviewed. Of all, 98.5% patients were aware of their condition. Surgery as a treatment for cataract was known to 57.6% respondents. 50.2% patients knew that during surgery, natural lens was replaced with an artificial lens. 89.2% believed that the cost of cataract surgery prevented people from seeking interventions, while 31.5% deemed it unaffordable. An acquaintance getting operated was the motivating factor for 47.3% patients. The principal barriers in seeking cataract treatment were found to be lack of accessibility and fear of pain in by 98% and 65.5% of patients respectively. Conclusion: Our study highlighted that majority of the respondents were aware of cataract as a disease, but the potential barriers preventing them from seeking treatment were accessibility, cost of surgery and personal belief. This study emphasizes the need for increasing the uptake of cataract services in the North Indian community. We apprehend that focused propagation of knowledge and communication will successfully enhance demand for cataract surgical services.